1979
DOI: 10.1071/mf9790365
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Observations on Cerithium moniliferum Kiener (Gastropoda : Cerithiidae) and its Trematode Parasites at Heron Island, Great Barrier Reef

Abstract: The distribution, abundance, growth and reproduction of a population of tropical intertidal gastropods, Cerithium moniliferum, at Heron Island, Great Barrier Reef, were examined and related to the incidence of parasitism by 11 digenean trematodes. The snails were patchily distributed on exposed beachrock, and showed little seasonally related change in abundance, but numbers and shell morphs were correlated with sand movements. Snails bred mainly in spring, had a thickened lip to the body whorl at this time and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Contrary to other systems in which abundant and widely dispersed molluscs can harbour several trematode species (e.g., Cannon 1979;Curtis 2009;Kube et al 2002), P. purpuratus harboured only three species (P. carvajali, Proctoeces sp. and an undetermined fellodistomid) that have already been reported in other studies (Aldana et al 2009;Muñoz et al 2012;Oliva et al 2010), despite the great abundance of the bivalve in the central rocky zone of Chile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to other systems in which abundant and widely dispersed molluscs can harbour several trematode species (e.g., Cannon 1979;Curtis 2009;Kube et al 2002), P. purpuratus harboured only three species (P. carvajali, Proctoeces sp. and an undetermined fellodistomid) that have already been reported in other studies (Aldana et al 2009;Muñoz et al 2012;Oliva et al 2010), despite the great abundance of the bivalve in the central rocky zone of Chile.…”
Section: Discussionmentioning
confidence: 99%
“…However, each trematode species has its own transmission strategy to infect the host; therefore, there are many other factors that are not associated with the season that affect egg and cercaria development (Koprivnikar and Poulin 2009;Lei and Poulin 2011;Pietrock and Marcogliese 2003;Rees 1948). Consequently, seasonal differences in the prevalence or abundances of trematodes in molluscs have been documented in some studies (Brown et al 1988;Fermer et al 2010;Olmos and George-Nascimento 1997;Tonn et al 1964), whereas others have not observed any seasonal patterns (Cannon 1979;Taskinen et al 1994). Taskinen et al (1994) have demonstrated seasonal infections based on indirect evidence, such as the frequency of the recent infection stages of sporocysts and the presence of miracidia in the aquatic media.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the diet of cleaner fish or the cleaning behavior of fish hosts could change if the parasite loads of fish change over time. Studies of temporal variation in fish parasites have been largely confined to cold temperate seas (Llewellyn 1959, Noble et al 1963, Kennedy 1975, Rawson 1976, with the few studies in the tropics restricted mostly to the parasites of snails (Rohde & Sandland 1973, Cannon 1978, 1979, Rohde 1981.…”
Section: Introductionmentioning
confidence: 99%
“…The findings on Cerithium agree to a certain degree with those of other authors. Stephenson and Searles (1960), Stephenson (1961), Moulton (1962) and Cannon (1979), drew attention to population fluctuations of this snail. According to Moulton, from November 1960 to January 1961 Cerithium had abandoned the beachrock' plateau' and began to concentrate at the southeastern end of the island.…”
Section: Discussionmentioning
confidence: 99%
“…Few such studies have been made. Rohde and Sandland (1973) and Cannon (1979) found some evidence for irregular 9 ~149149149149149149149149176 . .…”
Section: Introductionmentioning
confidence: 96%